Potassium in plants: Growth regulation, signaling, and environmental stress tolerance - Johnson, Riya; Vishwakarma, Kanchan; Hossen, Md. Shahadat; Kumar, Vinod; Shackira, A.M.; Puthur, Jos T.; Abdi, Gholamreza; Sarraf, Mohammad; Hasanuzzaman, Mirza (Plant physiology and biochemistry, 2022)
Potassium (K) is an essential element for the growth and development of plants; however, its scarcity or excessive level leads to distortion of numerous functions in plants. It takes part in the control of various significant functions in plant advancement. Because of the importance index, K is regarded second after nitrogen for whole plant growth. Approximately, higher than 60 enzymes are reliant on K for activation within the plant system, in which K plays a vital function as a regulator. Potassium provides assistance in plants against abiotic stress conditions in the environment. With this background, the present paper reviews the physiological functions of K in plants like stomatal regulation, photosynthesis and water uptake. The article also focuses upon the uptake and transport mechanisms of K along with its role in detoxification of reactive oxygen species and in conferring tolerance to plants against abiotic stresses. It also highlights the research progress made in the direction of K mediated signaling cascades. •Potassium has diverse role in plant growth and development.•Potassium is responsible for activation of several vital plant enzymes.•Potassium regulate water balance in plants and protect plants from abiotic stress-induced damages.•Potassium plays a vital role in mitigating oxidative stress in plants.